PERLINDUNGAN PEKERJA MIGRAN DARI PERSPEKTIF COMMUNITY DEVELOPMENT (STUDI KASUS DESA NYEROT KEC. JONGGAT KAB. LOMBOK TENGAH PROV. NUSA TENGGARA BARAT) - Okza Hendrian Wijaya; Budi Setiyono (Journal of Politic and Government Studies, 2020)
This research aims to explain how Migrant Workers Care Village works and how the program can strengthen Community Development in Nyerot village, Kec. Jonggat Kab. Lombok Tengah NTB. The method used in this study is a qualitative method with a case study approach, which is an approach to deepen a unique case. The results of the Strengthening of Community Development in the Nyerot village were marked by the increased awareness of the community and the Nyerot village government on PMI issues in the village through their participation in the Desbumi program. In addition, it was also strengthened by joint actions among community members in solving their own problems through the establishment of Nyerot village regulation no. 4 of 2015 concerning the protection of the Nyerot village PMI and the emergence of independence in the community through economic empowerment and the use of local community resources as subjects in the implementation of the Desbumi program.Keywords: Community Development, Desbumi, Indonesia Migrant Worker